2020
DOI: 10.1177/1548051820979634
|View full text |Cite
|
Sign up to set email alerts
|

How and When Humble Leadership Facilitates Employee Job Performance: The Roles of Feeling Trusted and Job Autonomy

Abstract: This study extends our understanding of humble leadership as an important trust-engendering leadership style that influences employee behaviors. Drawing on social exchange theory, we articulate how humble leaders’ employee-centric behaviors signal trust and facilitate a social exchange relationship between leaders and followers. Specifically, we posit that a leader’s humble leadership behaviors are positively related to employees’ task performance and organizational citizenship behavior via feelings of being t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 71 publications
1
37
0
Order By: Relevance
“…Research has indicated that feeling trusted is related to positive work outcomes for employees, such as enhanced task performance, job engagement and organizational citizenship behavior. 9 , 10 However, studies have also found that feeling trusted may have negative work outcomes. 8 , 44 We extended this research by exploring whether feeling trusted may also be related to negative outcomes in employees’ family domain (beyond the immediate workplace context).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research has indicated that feeling trusted is related to positive work outcomes for employees, such as enhanced task performance, job engagement and organizational citizenship behavior. 9 , 10 However, studies have also found that feeling trusted may have negative work outcomes. 8 , 44 We extended this research by exploring whether feeling trusted may also be related to negative outcomes in employees’ family domain (beyond the immediate workplace context).…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has found that feeling trusted can benefit both organizations and employees. 9 , 10 , 25 However, focusing on the positive effect of feeling trusted can mask the underlying costs. Recently, scholars have begun to focus on the dark side of feeling trusted and to challenge the prevailing conclusion that feeling trusted is always beneficial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leadership can determine employee's success. Hence, enhancing employee performance is inseparable from the role of the leaders (Cho et al, 2020;Kesari & Verma, 2018;Sandvik et al, 2019). Leadership is a personal ability of influencing employees to achieve company goals (Jyoti & Bhau, 2015;Zohar & Polachek, 2017) since fair leaders can transport mental support and respect which will enhance employees' performance.…”
Section: Introductionmentioning
confidence: 99%
“…Leadership is considered an important ability to improve and motivate employees to have a commitment in achieving organizational goals (Tyssen et al, 2014). Leadership can determine employee success; hence, enhancing employee performance is inseparable from the role of the leaders (Cho et al, 2020). Leadership is a person's ability to influence subordinates to work in achieving company goals (Zohar & Polachek, 2017) because fair leaders can provide mental support and being respectful will enhance employee performance.…”
Section: Introductionmentioning
confidence: 99%